Thin‐Metal‐Film‐Based Transparent Conductors: Material Preparation, Optical Design, and Device Applications (Advanced Optical Materials 3/2021). Issue 3 (4th February 2021) - Zhang, Cheng; Ji, Chengang; Park, Yong‐Bum; Guo, L. Jay
Abstract : Thin metal film stands out as a promising indium tin oxide (ITO)‐free transparent conductor, by its good optoelectronic performance, excellent mechanical flexibility, and simple fabrication process. In their Review (article number 2001298 ), Cheng Zhang, L. Jay Guo and co‐workers discuss the past progress and future challenges of ITO‐free transparent conductors that are based on thin metal films. This comprehensive review provides general guidelines of material selection, various techniques for preparing and characterizing high‐quality ultra‐thin metal films, and associated optical design principles for maximizing the conductor's performance. It also surveys both traditional and emerging applications. This review offers a valuable reference for researchers working on transparent conductors and optoelectronic devices using the same.